Developing marketing materials through interactive learning media suitable for vocational school - Vena Melliyani; Gia Nurapni; Fajar Sidik (Curricula: Journal of Curriculum Development, 2023)
This research aims to explore and develop marketing materials that are suitable for Vocational High School (SMK) 45 Lembang students through interactive learning media. Marketing is an important aspect in the business world that requires deep understanding and practical skills. In the context of vocational school education, the use of interactive learning media is considered an effective approach to increase students' understanding and involvement in the learning process, and this can also be useful if they want to continue their education at tertiary institutions where the domain is not much different from before. This research used a qualitative approach with descriptive methods focused on developing material through appropriate interactive learning media at SMK 45 Lembang to ensure that the material produced aligned with their needs and expectations. Data was collected using observation and interviews to students and teachers based on Google forms. The research objects were students at business vocational high schools and teachers who taught marketing courses.   Abstrak Di era digital ini, pendidikan di tingkat menengah, seperti di Sekolah Menengah Kejuruan (SMK), harus beradaptasi dengan cepat agar tetap relevan dan efektif dalam mempersiapkan siswa untuk memasuki dunia kerja. Salah satu aspek penting dalam pendidikan adalah pengembangan materi pembelajaran, terutama dalam bidang Marketing. Penelitian ini bertujuan untuk menggali dan mengembangkan materi Marketing yang sesuai untuk siswa Sekolah Menengah Kejuruan (SMK) 45 Lembang melalui media pembelajaran interaktif. Dalam konteks pendidikan SMK, penggunaan media pembelajaran interaktif dianggap sebagai pendekatan yang efektif untuk meningkatkan pemahaman siswa dan keterlibatan mereka dalam proses pembelajaran serta hal ini juga dapat bermanfaat jika ingin melanjutkan pendidikan di perguruan tinggi yang ranahnya tidak jauh berbeda dengan sebelumnya. Dalam penelitian ini, digunakan pendekatan kualitatif dengan metode deskriptif yang berfokus pada pengembangan materi melalui media pembelajaran interaktif yang sesuai di SMK 45 Lembang untuk memastikan bahwa materi yang dihasilkan sesuai dengan kebutuhan dan harapan mereka. Pengumpulan data diambil dengan observasi dan wawancara kepada peserta didik dan guru.   Kata Kunci: Pembelajaran interaktif; pembelajaran marketing; pengembangan materi pembelajaran